History and Prospects for the Integration of Paratransit in Transportation Planning in African Cities - (:unkn) unknown (My University, 2020)
This research examines the history of transportation planning in African cities and how paratransit has been taken into account in the production of planning documents. On the rise since the 1980s, paratransit today is the most common motorized transportation mode in many African cities. The dominant approach among policymakers has been to limit paratransit, in some cases even to ban it. The question this research explores is how distrust of paratransit, and underappreciation of its intrinsic qualities, have been reflected in urban transportation plans. Having selected two cities — Cape Town, South Africa and Nairobi, Kenya — we conducted an in-depth analysis of planning documents at national and local scales. South Africa has a long tradition of transportation planning, with documentation available at the national, provincial and municipal levels. In the 1990s, paratransit was a national level concern. It gradually became a municipal issue with the implementation of BRT. In Kenya, planning has a shorter history. Development agencies (e.g. JICA) have played a key role in recent planning processes and encourage the formalization of paratransit. However, planning documents contain no explicit references to ‘matatus’. In both cities, the focus in the documents is still mainly on developing infrastructure rather than improving mobility. While the role of paratransit is increasingly recognized, this trend is still more apparent in regulation than in planning.
Keywords: African Research